Perceived Value, Personality and Behavioural Intention of Electronic Brand Customers In Nairobi County, Kenya - Kibos, Kiprop Eric (Journal of Research in Marketing (ISSN: 2292-9355), 2019)
Electronic retail firms experience high customer turnover, frequent customer switching and complaint behavior which can be attributed to their focus on immediate brand sales with minimal focus on customers’ individual personalities and value perception. The study examined the moderating effect of personality on the relationship between perceived value and behavioural intention of electronic brand customers. The specific objectives of the study were to establish the: effect of customer, logistic and relationship values on behavioral intention and the effect of customer personality on the relationship between customers perceive logistic and relationship value and behavioral intention of electronic brand customers. The study was guided by: theory of reasoned action, personality theory and customer value models. The study adopted explanatory research design while the target population was 32,567 customers from which a sample of 400 respondents was obtained using multi-stage sampling procedure. Data was collected using questionnaires and analyzed using hierarchical regression. The results revealed that customer perceived relationship value (β =.246; p<.000) has significant influence on behavioural intention of electronic brand customers, while perceived logistic value (β =.049; p>000) does not. The findings also confirmed that customer personality has significant negative (β =-.053; p<.000) and positive (β =.046; p<.000) effect on the relationship between logistic and relationship values and behavioural intention of electronic brand customers. Therefore, relationship value significantly influence the behavioural intention of electronic brand customer, while perceived logistic value does not. In addition, personality partially moderates the relationship between perceived brand, logistic and relationship values and behavioural.